Hubungan Kecanduan Online Game dengan Depresi pada Remaja Laki-laki Pengunjung Game Centre di Kelurahan Jebres - Sofi Ariani; Djoko Suwito; Ruben Dharmawan (Nexus Pendidikan Kedokteran dan Kesehatan, 2012)
Background: The number of adolescent boys spending their time in the game center is growing considerably. Previous research revealed that online gaming addiction affected the physical and mental health. This study aims to seek the relationship between online game addiction and depression. Methods: This was a descriptive analytical research with a cross sectional approach. boys were sampled using purposive sampling method, based on inclusion and exclusion criteria. Depression was measured using BDI depression scale, while online game addiction was determined using Youngs questionnaire and Family Intimacy Instrument (CCI). Multiple logistic regression was used to analyse the relationship between online game addiction, depression and family intimacy using SPSS 17.0 for Windows. Results: The results indicated a positive relationship between online game addiction and depression among adolescent boys in Jebres village. Teenagers with online game addiction had 1.61 times greater the risk for depression than adolescent boys without online game addiction, although not statistically significant (OR=1.61; 95% CI=0.30 to 8.69) p=0.581). Result from analysis on family intimacy variable also showed non significant relationship with depression. Adolescent boys with low family intimacy had lower risk for depression (OR=0.44). However, online game addiction showed a greater relationship with depression than low family intimacy. Conclusions: There was a positive relationship between online game addiction and depression among adolescent boys in Jebres village although not statistically significant. The higher the level of addiction to online games, the higher the risk for depression. Keywords: Adolescent, Online game addiction, Depression, Family intimacy.